Expression of p38 mitogen‐activated protein kinase (p38MAPK) and pathological change in intussusception. Issue 9 (13th April 2016) - Guo, Wan‐liang; Wang, Jian; Liu, Chi; Yang, Fu‐bin; Li, Shao‐wei
Abstract: Background: The aim of this study was to develop a mouse model and further assess the pathological changes associated with the expression of p38mitogen‐activated protein kinase (p38MAPK) in intussusception. Methods: Sixty‐two adult Balb/C mice were used. A longitudinal incision was made in the middle rectus muscle in the body cavity. The ileum was intussuscepted into the colon. Measurements were taken at the onset of intussusception and at 5, 15, 30, 60, and 120 min. Mucosal impairment was assessed on microscopy. Ten of the intussuscepted mice were used as an ischemia–reperfusion (I/R) model. Immunohistochemistry was used to assess expression of p38MAPK in the I/R model and pediatric patients specimens of intussusception. Results: The intussusception model was successfully established in 46 mice. After 15 min, vascular compromise became visible in these 46 mice. Over time, vascular function worsened. There were significant differences in microscopy injury score in the intestinal mucosa between the 15 min and 30 min groups ( P = 0.0006), 30 min and 60 min groups ( P = 0.0046), and the 60 min and 120 min groups ( P = 0.0050). There was no significant difference between the 5 min and 15 min groups ( P = 0.0597). p38MAPK was expressed strongly in pediatric specimens of intussusception. Immunostained sections of intestinal epithelium had significantly higher mean quick score for p38MAPK in the intussusception I/R model group than in the intussusception group and controls ( P = 0.0130). On each two‐group comparison there was a significant difference between groups (all P < 0.01; Fig. 7 ). Conclusions: The present mouse model can be used to assess the dynamic pathological changes associated with intussusception. I/R is associated with upregulation of p38MAPK in intussusception.